2013
DOI: 10.1007/s10877-013-9468-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a mathematical model of apoptosis: individual differences and malfunction in programmed cell death

Abstract: Apoptosis is an important area of research because of its role in keeping a mature multicellular organism's number of cells constant hence, ensuring that the organism does not have cell accumulation that may transform into cancer with additional hallmarks.Firstly, we have carried out sensitivity analysis on an existing mitochondria-dependent mathematical apoptosis model to find out which parameters have a role in causing monostable cell survival i.e., malfunction in apoptosis. We have then generated three heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…It highlights the interesting role of IAP protein in controlling the cell-to-cell variability of intrinsic apoptosis response, and suggests that in treating diseases exploiting the apoptosis mechanism, such as cancer, the IAP protein offers a potential therapeutic target not only for effective modulation of apoptosis [74] but also for eliminating the undesired cell-to-cell heterogeneity, a major obstacle to effective cancer treatment and personalized medicine [75]. This finding is in line with the current view of the therapeutic function of IAP based on the study of apoptosis pathway at cell population level [17,76]. …”
Section: Resultsmentioning
confidence: 56%
“…It highlights the interesting role of IAP protein in controlling the cell-to-cell variability of intrinsic apoptosis response, and suggests that in treating diseases exploiting the apoptosis mechanism, such as cancer, the IAP protein offers a potential therapeutic target not only for effective modulation of apoptosis [74] but also for eliminating the undesired cell-to-cell heterogeneity, a major obstacle to effective cancer treatment and personalized medicine [75]. This finding is in line with the current view of the therapeutic function of IAP based on the study of apoptosis pathway at cell population level [17,76]. …”
Section: Resultsmentioning
confidence: 56%
“…Importantly, the addition of these nodes in the model and their experimental is a clear advance of our study with respect to other models, and better recapitulates the behaviour of the system in cells and the enhances the Importantly, our model confirms the existence of bistability in accordance with other studies of the apoptosis network 20,21 . However, many studies modelling apoptosis focused on the extrinsic pathway consisting of death receptor activation, subsequent activation of caspases and secondary activation of the mitochondrial pathway 22,23,67,68 , or the processes upstream of caspase activation such as BCL2 protein regulation of MOMP [21][22][23]69,70 . Other modelling studies that concerned the activation of caspases in the intrinsic pathway did either not look at the control of bistable properties 22,67,69 , or did not include BAX and SMAC 19,20,23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies modelling apoptosis focused on the extrinsic pathway consisting of death receptor activation, subsequent activation of caspases and secondary activation of the mitochondrial pathway 22,23,67,68 , or the processes upstream of caspase activation such as BCL2 protein regulation of MOMP [21][22][23]69,70 . Other modelling studies that concerned the activation of caspases in the intrinsic pathway did either not look at the control of bistable properties 22,67,69 , or did not include BAX and SMAC 19,20,23 . A notable exception is the work by Tyson and colleagues 21 , which provided and excellent account of which network nodes and parameters regulate the bistability properties, in particular 1 irreversibility, time-delay and threshold.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3, compared with control group, wound healing rate was slowed to 22.82%, and inhibition ratio reached to 96.39%, respectively, which obviously indicated that Previous studies have shown that tumorigenesis is associated with malfunction of cell apoptosis. 35 However, apoptosis is one of the critical mechanisms of the anti-tumor agents. It had been also observed that the apoptosis rate increased in a dosedependent manner in the HCC1806 cell lines aer 5 was added.…”
Section: Discussionmentioning
confidence: 99%